First Report of Amphiplatyspora striata Kundu and Haldar, 1984 from Chondracisrosea (Order: Orthoptera) of Manipur, India. - N. Mohilal, Indira Yumnam,; Shah, M. Manjur (International Multidisciplinary Research Journal)
The present communication deals with the complete life history of a Septate Gregarine (Protozoa:Sporozoa) found in Grasshoppers. Gregarines found in the mid-gut region of Grasshoppers were collected and examined for parasites. A species belonging to the genus Amphiplatysporawas obtained from Chondracisrosea. The morphology of the gregarine and its affinities with the other genera of the family Amphiplatysporidae [3] are discussed. The morphological details of the different stages supported with photomicrographs are also provided.